The impact of religious education in mitigating the effects of family environment on students' mental health - Shodiq, Sadam Fajar; Makrufi, Anisa Dwi; Dahliyana, Asep; Valencia, Nadira Putri; Nurunisa, Fadhila Aisyah; Goselfa, Limason (Frontiers in Education, 2025)
The mental health of students is a significant issue, particularly in the face of the difficulties posed by a complicated familial setting. The significance of religious education in mitigating the impact of the family environment on students' mental health is gaining prominence, particularly in major Indonesian cities like Surabaya, Jakarta, Yogyakarta, and Bandung. This study encompassed a total of 498 senior high school students residing in four major cities in Indonesia. The association between family environment, religious education, and students' mental health was assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and the bootstrapping approach for data analysis. The findings indicated that religion education had a crucial role as a moderator in the relationship between family environment and the mental health of pupils. Religious education enhanced students' ability to withstand pressure from an unsupportive familial context and had a beneficial impact on students' mental health. This study emphasizes the significance of incorporating religious education inside the family as a means of promoting students' mental health. The practical implication of this study is the creation of educational programs that prioritize enhancing religious values inside the family as a strategic measure to enhance the mental health of pupils.